Adaptive developmental plasticity in rhesus macaques: the serotonin transporter gene interacts with maternal care to affect juvenile social behaviour. Issue 1881 (20th June 2018) - Madrid, Jesus E.; Mandalaywala, Tara M.; Coyne, Sean P.; Ahloy-Dallaire, Jamie; Garner, Joseph P.; Barr, Christina S.; Maestripieri, Dario; Parker, Karen J.
Abstract : Research has increasingly highlighted the role that developmental plasticity—the ability of a particular genotype to produce variable phenotypes in response to different early environments—plays as an adaptive mechanism. One of the most widely studied genetic contributors to developmental plasticity in humans and rhesus macaques is a serotonin transporter gene-linked polymorphic region (5-HTTLPR), which determines transcriptional efficiency of the serotonin transporter gene in vitro and modifies the availability of synaptic serotonin in these species. A majority of studies to date have shown that carriers of a loss-of-function variant of the 5-HTTLPR, the short (s) allele, develop a stress-reactive phenotype in response to adverse early environments compared with long (l) allele homozygotes, leading to the prevalent conceptualization of the s-allele as a vulnerability allele. However, this framework fails to address the independent evolution of these loss-of-function mutations in both humans and macaques as well as the high population prevalence of s-alleles in both species. Here we show in free-ranging rhesus macaques that s-allele carriers benefit more from supportive early social environments than l-allele homozygotes, such that s-allele carriers which receive higher levels of maternal protection during infancy demonstrate greater social competence later in life. These findings provide, to our knowledge, the first empirical support for the assertion that the s-allele grants high undirected biological sensitivity to context in primates and suggest a mechanism through which the 5-HTTLPR s-allele is maintained in primate populations.